Programma: 6 december Timemachine; 7 december Reprazent, Femi Kuti & The Positive Force; 8 december Insane Clown Posse; 9 december Tindersticks, 10 december Tha Alkaholiks; 11 december What's new, "The Box" talentscout tour finale - Zero, (1997)
Programma: 6 december Timemachine; 7 december Reprazent, Femi Kuti & The Positive Force; 8 december Insane Clown Posse; 9 december Tindersticks, 10 december Tha Alkaholiks; 11 december What's new, "The Box" talentscout tour finale.